Shivalinga : Symbolism, Typology and a Glance on Licchavi Shivalingas - Khanal Parajuli, Sandhya (Nepalese Culture, 2021)
The images that look like a male and a female organ have been discovered around the world and are marked as sacred since the establishment of civilization. What does this image symbolize? Why do Hindus worship it and why is it personified as lord Shiva? The concentration to answer these queries through descriptive analysis of the linga is tried in this article. Lingas are found in various civilizations, including Indus valley, but the perception varies. Its tangible and intangible form and several varieties are its typology. This article is mainly based on symbolism of linga for various societies and for earlier Aryans. Linga, though varies in form, is a phallic symbolism of creation which was not accepted by the Aryans at first due to its nudity and straightforwardness. But after the realization of its core theme that the linga is the composition of prakriti and purush, it made them eager to establish through its reformed reality rather than his anthropomorphic form in honor of their supreme god, the creator and a destroyer, no other than lord Shiva who self-emerged as jyotirlinga. Almost all the typologies including maximum varieties of manmade lingas are found around Kathmandu valley but the choice of Licchavis for the establishement of linga with its specific typology and theme are discussed.